Genetic diversity of campomanesia adamantium and its correlation with land use and land cover - Crispim B.D.A. (2021)
© 2021 by the authors. Licensee MDPI, Basel, Switzerland.(1) Background: Campomanesia adamantium is an endemic species of the Cerrado and this biome has been under threat by its constant degradation. The genetic diversity of C. adamantium was characterized using species-specific microsatellites in two different time periods and correlations of these parameters of genetic diversity with the land use and land cover data. (2) Methods: We used 10 microsatellite loci to analyze C. adamantium from five populations, collected in 2011 and 2017. Maps of land use and land cover of the collection sites in both years were generated and subsequently correlated with genetic diversity. (3) Results: No significant loss of genetic diversity was observed in the analyzed period and a positive inbreeding coefficient was observed in all populations. AMOVA and STRUCTURE showed that there is no population structure between years and populations. Significant Pearson correlations were observed in 2017 between parameters of genetic diversity and land use and land cover, with a positive correlation between expected heterozygosity and secondary vegetation, and a negative correlation between inbreeding coefficient and exposed soil. (4) Conclusions: There was no decline in genetic diversity from 2011 to 2017. The high rates of the inbreeding coefficient could lead, for the species, in the long run, to an inbreeding depression as the Cerrado fragmentation might cause a population bottleneck.